Penerapan Model Pembelajaran Kooperatif Pendekatan Struktural Numbered Heads Together (NHT) Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VII.1 SMP Negeri 5 Tambang - Sari, Yulia Purnama Sari Purnama; Roza, Yenita Roza; ', Zuhri D (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to improve learning process and mathematics learning outcomes in SMP Negeri 5 Tambang by implementing cooperative learning approach to structural numbered heads together. Subjects of the research were students grade VII.1 who have the academic ability of the heterogeneous. This research is a classroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score, increasing the number of students who scored 20 and 30 compared to the development of the number of students who received grades 5 and 10 as well as the increase in the average value of students from the first cycle to the second cycle. Based on the results, we can conclude the implementation of cooperative learning model Numbered Heads Together (NHT) structural approach can improve student’s mathematics learning outcomes. Key words: cooperative learning, NHT structural approach, learning outcomes